CURIO - Xie, Xiuyun (2017)
CURIO seeks to investigate and understand basic curious questions that we might have asked but never got around to ponder upon. Often disguised as passing questions or thoughts, what if they were scrutinized and researched like how an epistemophilia person would? This project aims to understand what it takes to be more in touch with my subtle curious questions and presenting newly learned knowledge using illustration as a medium.